Plant Origin Regulates the Response of Solidago canadensis Reproductive Traits to Long-Term Warming and Nitrogen Addition - Xiaohui Zhou; Xin Chen; Xin Luo; Yanling Wu; Juanjuan Li; Jianxin Ren; Jingji Li (Plants)
Climate warming and nitrogen (N) deposition have already occurred and will continue to occur, profoundly affecting exotic plant invasion. Most studies on the effects of climate change focus on plant growth, biomass, and leaf traits, with limited reports on reproductive responses. We selected Solidago canadensis from North America and China as focal species and conducted a long-term common garden experiment simulating climate warming and N deposition to examine how climate warming, N addition, and plant origin influence its reproductive traits. Chinese Solidago canadensis exhibited significantly greater ramet height, more robust ramet diameters, longer and wider inflorescences, and higher seed mass compared to North American Solidago canadensis. Long-term warming and plant origin alone or in combination significantly influenced reproductive traits, while N addition did not influence these traits. The vegetative propagation of a native population was sensitive to warming and N addition, while the generative propagation of an invasive population was sensitive to their combined effects. These findings suggest that the reproductive strategies of Solidago canadensis varied with their origin, and plant origin might be important in mediating climate change effects on their reproduction under plant invasion.